The Inhibitory effect of pyocyanin pigment produced byPseudomnas aeruginosa on biofilm formation of Klebseila pneumoniae (Journal of the College of Basic Education, 2022)
The Pyocyanin was extracted from clinical isolate of Pseudomonas aeruginosa that isolated from patient suffering from cystic fibrosis ; and the Klebsiella pneumoniae and Klebsiella oxytoca isolates werecollectedfrom Catheter Associated Infections (CAI) and Urinary tract infection (UTI) patients with 25 (20.49%) and 3 (2.54%)of total 122 urine specimens respectively; represented the degree of the biofilm thickness among 25 isolates of K. pneumoniae, 3(12%) isolates (K21, K42 and K129) were considered as good producers of biofilm after incubation for 24 h at 37ºC and evaluated by using crystal violet staining solution technique and their optical density (O.D) was determined at 540 nm. The susceptibility pattern ofantibiotics against K. pneumoniae isolates (K21 and K42) were showed resistant to Ceftriaxon, Cefotaxime, Piperacillin, Metronindazole, Cephalothin and Ceftazidime whereas sensitive to Imipenem, Gentamicin, Tobramycin, Amikacinand Ciprofloxacin; However, K129 was shown different behavior against same antibiotics. The biofilm of K21, K42 and K129 were reduced significant differences (P<0.05) after treatment with (2048µg/ml) of the pyocyanin solution comparatively with differences MIC values of sensitive antibiotics for these isolates after incubated for 24 h at 37 ºC; the viablecells count of these isolates were shown insignificant differences (P<0.05). The pyocyanin solution has an inhibitory effect on planktonic isolates K21, K42 and K129 were shown increased diameter of inhibition zones with increased concentration after incubated for 24 h at 37 ºC.Keywords: Inhibitory effect, catheter, Pseudomonas aeruginosa, pyocyanin, K. pneumoniae and biofilm.